CD8+ T lymphocyte is a main source of interferon-gamma production in Takayasu’s arteritis - Yan-Long Ren (Nature Portfolio, 2021)
Abstract Interferon-gamma (IFN-γ) is a cytokine involved in the pathogenesis of Takayasu’s arteritis (TAK). However, the source of IFN-γ in TAK patients is not fully clear. We aimed to investigate the source of IFN-γ in TAK. 60 TAK patients and 35 health controls were enrolled. The lymphocyte subsets of peripheral blood were detected by flow cytometry, cytokines were detected by Bio-plex. The correlation among lymphocyte subsets, cytokines and disease activity indexes was analyzed by person correlation. The level of serum IFN-γ in TAK patients was significantly increased (P < 0.05). The percentage of CD3+IFN-γ+ cells in peripheral blood CD3+ cells was significantly higher in TAK patients than that of healthy control group (P = 0.002). A higher proportion of CD3+CD8+IFN-γ+ cells/CD3+IFN-γ+ cells (40.23 ± 11.98% vs 35.12 ± 11.51%, P = 0.049), and a significantly lower CD3+CD4+IFN-γ+/ CD3+CD8+IFN-γ+ ratio (1.34 ± 0.62% vs 1.80 ± 1.33%, P = 0.027) were showed in the TAK group than that of control group. The CD3+CD8+IFN-γ+/CD3+IFN-γ+ ratio was positively correlated with CD3+IFN-γ+cells/ CD3+cells ratio (r = 0.430, P = 0.001), serum IFN-γ level (r = 0.318, P = 0.040) and IL-17 level (r = 0.326, P = 0.031). It was negatively correlated with CD3+CD4+IFN-γ+/CD3+IFN-γ+ ratio (r = − 0.845, P < 0.001). IFN-γ secreted by CD3+CD8 + T cells is an important source of serum IFN-γ in TAK patients.